Extracorporeal membrane oxygenation combined with continuous renal replacement therapy in cutaneous burn and inhalation injury caused by hydrofluoric acid and nitric acid. Issue 48 (December 2017) - Pu, Qinhua; Qian, Jinxian; Tao, Weiyi; Yang, Aixiang; Wu, Jian; Wang, Yaodong
Abstract: Rationale: Hydrofluoric acid (HF) is a highly corrosive agent and can cause corrosive burns. HF can penetrate deeply into tissues through intact skin and the lipid barrier, leading to painful liquefactive necrosis, and inducing hypocalcemia and hypomagnesemia. In this study, we hypothesize that continuous renal replacement therapy (CRRT) may be beneficial in addressing hemodynamic instability in cases of HF poisoning. Patient concerns: A 25-year-old man fell into an electroplating pool containing 10% HF and 50% nitric acid. Diagnoses: He had severe cutaneous injuries involving approximately 60% of his total body surface area including the head, face, neck, right upper arm, right hand, trunk, perineum, and both lower limbs and feet. Examination at admission showed the following electrolyte concentrations: ionic calcium 0.192 mmol/L, total calcium 0.72 mmol/L, magnesium 0.4 mmol/L, potassium 5.49 mmol/L, and sodium 136.8 mmol/L. Interventions: An initial 20 mL intravenous bolus of 10% calcium gluconate was followed by a continuous infusion at 6 g/h plus continuous intravenous drip 25% magnesium sulfate at 1.5 g/h. Continuous cardiac monitoring was performed in the intensive care unit. Extracorporeal membrane oxygenation (ECMO) was used to improve oxygenation function at 38 hours post exposure. Antibiotic therapy using imipenem/cilastin plus vancomycin was required. Outcomes: After treatment for 12 hours, electrolyte concentrations returned to normal. On day 11, the hemodynamic parameters were stable and oxygenation function had improved. On day 26, the patient was weaned off CRRT. One month later, the patient twice received skin grafting, then was discharged from the hospital without pulmonary, cardiac, or neurological complications 3 months later. Lessons: The present case study demonstrates that CRRT may be an effective and potentially lifesaving therapy after severe exposure to HF. Prolonged hemodialysis is recommended to remove delayed release fluoride ions to avoid delayed systemic injury. When conventional therapy can not improve oxygenation and/or carbon dioxide retention, ECMO should be performed as soon as possible.